Insights into Liquid Product Formation during Carbon Dioxide Reduction on Copper and Oxide-Derived Copper from Quantitative Real-Time Measurements - Löffler, Mario; Khanipour, Peyman; Kulyk, Nadiia; Mayrhofer, Karl; Katsounaros, Ioannis (ACS Catalysis, 2020)
We quantify the formation rates and faradaic efficiencies for liquid products of CO2 reduction on copper and oxide-derived copper in real time, in a single potential sweep. Compared with classical offline product analysis, the electrolyte characterization near the electrode favors the formation of aldehydes versus alcohols. When the CO2 reduction takes place in the presence of an aldehyde, the formation of the respective alcohol is enhanced, both in terms of onset potentials and partial current densities. The above imply that aldehydes and alcohols are formed sequentially. All determined products are formed at lower overpotential on oxide-derived copper, indicating that the electrode treatment generates different, more active sites. Overall, the presented methodology based on proton-transfer-reaction mass spectrometry can complement hard electron ionization by monitoring the transient formation of liquid products under dynamic conditions.
CRIS-Team WoS Importer:2020-07-17